Peritonitis Due To Hollow Viscus Perforation, A Clinical Retrospective Study in A Tertiary Health Care - Mohapatra, Ashisbala; Mohapatra, Abinasha; Bairisal, Pragyan Paramita (Journal of Neonatal Surgery, 2025)
Background - Peritonitis is defined as inflammation of the serosal membrane that lines the abdominal cavity and the organs contained in it. The introduction of infection into the sterile peritoneal environment through a bowel perforation and introduction of a chemically irritating material like gastric acid from a perforated ulcer causes peritonitis. Aim and Objective - To study the frequency of peritonitis secondary to hollow viscus perforation in relation to age, sex, anatomical location, symptoms and signs, reliability of investigation like Erect x-ray abdomen. Material and Method - This is a retrospective study based on the analysis of 50 cases of hollow viscous perforation admitted to General Surgery Department, F.M.Medical College and Hospital, Balasore, Odisha from December 2023 to November 2024. Results - Most of the patients with hollow viscous perforation were above the age of 50 years, followed by the age group of 30-39 years. Maximum number of patients were found to be males (82%). Females constituted about 18% of the study group. Most common presenting symptom was abdominal pain. Conclusion - Laparotomy with the closure of the perforation with an omental patch (66%) is the commonest operative management for perforated peptic ulcer.